Economic incentives for the voluntary disclosure of current cost financial statements - Wong, Jilnaught (Journal of Accounting and Economics, 1988)
This study examines why some New Zealand listed companies voluntarily present current cost financial statements. The results suggest that tax and political cost considerations are influential in the voluntary disclosure of current cost information.